Evaluation of the Impact of R&D on the Socio-Economic Development of EU Countries - Romualdas Ginevičius; Eigirdas Žemaitis; Vladislavas Petraškevičius (Amfiteatru Economic)
Investment in R&D varies widely in EU countries, both in terms of its overall volume and the sources of investment, business, the state, and higher education institutions. To a large extent, the volume of investment depends on the state of economic development of the country. Economically developed EU countries are dominated exclusively by business investments, while investments in higher education play a limited role. This is because higher education institutions perform a large part of R&D together with businesses. In developing countries, investment in R&D is equally distributed between business, the state, and higher education institutions. This is because scientific business research opportunities are still limited in these countries. To adequately determine the impact of R&D investments on the economic development of countries, the overall size of R&D investment needs to be transformed in such a way as to assess its internal structure in which business and higher education institutions have the highest importance. Investments in R&D have a lower direct impact on a country’s social development compared to the impact on economic development. This is because R&D affects economic development directly through technological innovations and social development indirectly through economic development.